Penyelenggaraan Walīmah ul-Ursy di Jalan Umum Perspektif Hukum Islam dan Hukum Nasional - Sri Tantini; Nila Sastrawati (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab dan Hukum, 2021)
This article aims to describe and analyze related to wedding parties (walimah al-ursy) which are held on public roads, viewed from the perspective of Islamic law and national law which are then linked to what happened in Ex. Nambo Lempek, Kec. Nambo, Kab. Banggai, Central Sulawesi. In answering the problems above, the author uses Field Research, namely research that raises data and problems in the field (research location). The sources of data obtained include primary data and secondary data. This study uses a type of qualitative research using an empirical juridical approach, namely to find out how a law is implemented and how the process is enforced.The results of this study indicate that in Ex. Nambo Lempek Kec. Nambo Kab. Banggai, Central Sulawesi, there are still many public road closure activities that are not in accordance with statutory regulations. Good road closures for weddings, thanksgiving events, circumcisions, and akikah. Even though Islamic law and national law both have the same view regarding the issue of organizing a wedding party (walimah al-ursy) in Islamic law road closures are allowed on the condition that they leave part of the road so that other road users can continue to pass and safety can be maintained. Meanwhile, in national law, the use of public roads for weddings is allowed as long as there is a valid permit and alternative roads and temporary traffic signs are installed